NATIONAL SECURITY AND DISCOURSE FRAMING IN POST-SOVIET SPACE - Rabotyagova, I. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The paper is dedicated to the factors that influence discourse framing in Post-Soviet space, that makes information be presented in a particular way. The national security question depends on how citizens estimate and reproduce nominations created by the governments in order to integrate and to mobilize masses to the particular actions. The perspectives of discourse framingare presented.